Complementarity analysis of consequent-pole bearingless flux reversal motor windings with different pitch matchings - YiFei Yang; Jie Liu; RenZhong Wang; HongBin Wang (AIP Advances, 2022)
First, a topology of a consequent-pole bearingless flux reversal (CPBFR) motor suitable for flywheel battery magnetic suspension support systems is proposed, and the specific forms of different winding pitches are analyzed. Then, the phenomenon of winding complementarity, which is unique to certain permanent magnet bearingless motors, is explained theoretically. The magnetic density distribution characteristics of the no-load air gap of the consequent-pole permanent magnet rotor are given, and the influence of different winding pitches on the no-load induced potential as well as the influence of different winding pitches on no-load induced potential harmonics are revealed. Finally, the working feasibility of the CPBFR motor is verified from the perspective of magnetic field distribution and the magnetic line of force.